The molecular genetics of the Notch locus in Drosophila melanogaster. - Grimwade, B.G.; Muskavitch, M.A.; Welshons, W.J.; Yedvobnick, B.; Artavanis-Tsakonas, S. (Developmental Biology, 1985)
The Notch locus of Drosophila melanogaster profoundly affects differentiation of the central nervous system in the early embryo. Previous molecular studies suggested that the locus spans 40 kb of DNA and encodes a 10.5-kb poly(A)+ RNA. The results of genetic, cytogenetic, and molecular studies of newly induced and preexisting Notch alleles are reported. Molecular analysis of 5' flanking mutations defines a distal limit for the locus, and transcriptional activity of Notch in relation to that of flanking transcription units provides evidence regarding the proximal limit. Examination of a set of mutable alleles implicates a foldback transposable element as the basis of chromosomal instability, and shows that insertion sequences within the locus do not necessarily result in a mutant phenotype. The results are discussed with regard to existing developmental and genetic analyses, and a molecular model is proposed that attempts to explain the pleiotropic action of Notch.